2006
DOI: 10.1590/s0100-879x2006001100012
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of the dichloromethane fraction from Vernonia scorpioides (Lam.) Pers. (Asteraceae) against Ehrlich's tumor cells in mice

Abstract: Vernonia scorpioides has been widely used in Brazil to treat skin problems and chronic wounds, such as ulcers of the lower limbs and diabetic lesions. In the present study, we investigated the effect of a dichloromethane (DCM) fraction of V. scorpioides leaf extract on Ehrlich ascitic and solid tumor-bearing mice. The animals were treated once a day with the DCM fraction at a concentration of 5 mg/kg, administered ip during and after the development of the tumor. The lifespan, weight, number and type of leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
1
9
0
2
Order By: Relevance
“…The subfraction used in this experiment, SF2125, was obtained from DCM fraction, confirms the toxic properties of these compounds. In this study, we showed that the SF 2125, obtained from the chromatographic fractionation of the DCM fraction of V. scorpioides had the same activity showed by Pagno et al, 2006. Treatment with SF-2125 totally inhibited the development of the ascetic tumor S180 when in direct contact with tumor cells, as also demonstrated through in vitro intraperitoneal administration, in loco, to the ascitic tumor development.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The subfraction used in this experiment, SF2125, was obtained from DCM fraction, confirms the toxic properties of these compounds. In this study, we showed that the SF 2125, obtained from the chromatographic fractionation of the DCM fraction of V. scorpioides had the same activity showed by Pagno et al, 2006. Treatment with SF-2125 totally inhibited the development of the ascetic tumor S180 when in direct contact with tumor cells, as also demonstrated through in vitro intraperitoneal administration, in loco, to the ascitic tumor development.…”
Section: Discussionsupporting
confidence: 59%
“…When applied immediately after inoculation of the tumor cells in vivo, it totally abolished the tumor development, and when treatment began 3 days after the tumor challenge, the tumor development was decreased, sustaining a probable antineoplastic activity. The fact of the intravenous treatment did not reduce the ascitic tumor volume, suggest that some enzymatic route could be deactivating the systemic via, according with previous results, where mice treated by oral via with DCM fraction of V. scorpioides did not reduce Ehrlich´s ascitic or solid tumor (Pagno et al, 2006). Among the Vernonia species, some cytotoxicity has been described for isolated sesquiterpene lactones from V. cinerea (Kuo et al, 2003) and V. lasiopus (Koul et al, 2003).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous studies of V. scorpioides crude extract and its derived chloroform and hexane fractions have shown fungicide and moderate bactericide activity (Freire et al, 1996), and its use as a treatment for mange (scabies) has been recorded (Lans et al, 2001). In mice, the dichloromethane fraction (5 mg/kg) from the crude extract totally inhibited tumor development (Pagno et al, 2006), while subfraction 2125 from the crude extract (5mg/kg) inhibited tumor growth in the Sarcoma 180 ascitic tumor model in mice (Kreuger et al, 2009). The topical use of its alcoholic extract (200 mg of the V. scorpioides hydrogel) showed mild wound healing effects in rats when the wounds were treated topically for 30 days (Leite et al, 2002), although noninfected skin ulcers treated with an ointment 20% of the crude concentrated extract from V. scorpioides with solid Vaseline and lanoline (1:2) showed toxicity for the tissues when applied immediately after the incision in mice.…”
Section: Introductionmentioning
confidence: 99%